Polypharmacology of conformationally locked methanocarba nucleosides. Issue 12 (December 2017) - Jacobson, Kenneth A.; Tosh, Dilip K.; Toti, Kiran S.; Ciancetta, Antonella
Graphical abstract: Highlights: Weak off-target activity of nucleosides at novel targets can be optimized. Conformationally constrained nucleosides are privileged scaffolds. The affinity and selectivity at conventional nucleoside targets can be enhanced. Unconventional targets are the dopamine transporter and non-purine GPCRs. Abstract : A single molecular scaffold can be adapted to interact with diverse targets, either separately or simultaneously. Nucleosides and nucleotides in which ribose is substituted with bicyclo[3.1.0]hexane are an example of a versatile drug-like scaffold for increasing selectivity at their classical targets: kinases, polymerases, adenosine and P2 receptors. Also, by applying structure-based functional group manipulations, rigidified adenosine derivatives can be repurposed to satisfy pharmacophoric requirements of various GPCRs, ion channels, enzymes and transporters, initially detected as off-target activities. Recent examples include 5HT2B serotonin receptor antagonists and novel dopamine transporter allosteric modulators. This directable target diversity establishes rigid nucleosides as privileged scaffolds. Teaser: The scope of action of nucleosides, widely used anticancer and antiviral drugs, is now extended to unconventional targets, including diverse receptors, enzymes and transporters, using a conformational lock.